2018
DOI: 10.1212/wnl.0000000000004844
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in CSF as prodromal biomarkers for Huntington disease in the PREDICT-HD study

Abstract: Objective To investigate the feasibility of microRNA (miRNA) levels in CSF as biomarkers for prodromal Huntington disease (HD).Methods miRNA levels were measured in CSF from 60 PREDICT-HD study participants using the HTG protocol. Using a CAG-Age Product score, 30 prodromal HD participants were selected based on estimated probability of imminent clinical diagnosis of HD (i.e., low, medium, high; n = 10/ group). For comparison, participants already diagnosed (n = 15) and healthy controls (n = 15) were also sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…First, miRNAs are particularly enriched in the mammalian brain (Nelson et al, 2008), are important in regulating neural activity (Tan et al, 2013), and could potentially serve as biomarkers for brain diseases (Reed et al, 2018). Second, the small footprint of miRNA sites facilitates packaging into virus, an important mode of gene delivery to post-mitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…First, miRNAs are particularly enriched in the mammalian brain (Nelson et al, 2008), are important in regulating neural activity (Tan et al, 2013), and could potentially serve as biomarkers for brain diseases (Reed et al, 2018). Second, the small footprint of miRNA sites facilitates packaging into virus, an important mode of gene delivery to post-mitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Reed et al [ 159 ] suggested that six miRNAs: miR-135b-3p, miR140-5p, miR-520f-3p, miR-8082, miR-4317 and miR-3928-5p were considerably elevated in presymptomatic HD patients, thus, representing valuable biomarkers for the early diagnosis of the disease. Another study revealed that the plasma level of miR-34b was sharply reduced in presymptomatic HD patients compared with controls, indicating that miR-34b may be a novel biomarker of HD, which can be steadily expressed in the plasma and identified before clinical symptoms [ 151 ].…”
Section: Mirna Dysregulation and Mitochondrial Dysfunction In Alzhmentioning
confidence: 99%
“…Because CSF circulates in a closed system and is in direct exchange with the brain parenchyma, it is a promising biomarker source for neurodegenerative diseases that might provide more specific insights into the cellular disease-mechanisms as compared to blood. miRNA profiles in CSF were shown to discriminate healthy controls from patients with different neurological diseases ( Dangla-Valls et al, 2017 ; Marques et al, 2017 ; Reed et al, 2018 ).…”
Section: Sources Technical Considerations and Biomarker Potential Ofmentioning
confidence: 99%